Valsalva Retinopathy Associated with Sexual Activity - Khalid Al Rubaie; J. Fernando Arevalo (Case Reports in Medicine)
A 54-year-old healthy male presented complaining of sudden loss of vision in the right eye. Initial visual acuity was counting fingers. The patient’s acute vision loss developed after sexual activity. Color fundus photos and fluorescein angiography were performed showing a large subinternal limiting membrane hemorrhage in the macular area. A 23-gauge sutureless pars plana vitrectomy with brilliant blue assisted internal limiting membrane peeling was performed with best-corrected visual acuity recovery to 20/50 at 6 months of followup.